Effect of nano nitrogen and phosphorus on yield and quality of ber (Ziziphus mauritiana) (Current Horticulture, 2024)
An experiment was conducted at Agricultural Research Station, Mandor, Jodhpur (Rajasthan) to find out the effects of nano nitrogen  and phosphorus fertilizers on growth, yield and quality of ber (Ziziphus mauritiana Lam.) using factorial randomized block design  with 5 replications during October 2021 to March 2022. There was maximum plant height (6.45 %, 79.17 cm), number of primary  branches (14.72), secondary branches (22.09), chlorophyll contents (55.34 SPAD), fruit volume (20.63cm3), specific gravity (0.95),  fruit length (3.42 cm), fruit diameter (3.16 cm), pulp thickness (12.56 mm), pulp weight (15.79 g), pulp: stone ratio (19.20),fruit setting  (6.92 %), average fruit weight (18.00 g), yield/ tree (64.57 kg), ascorbic acid (vitamin-C) (65.75 mg/100g pulp), total soluble solid  (15.77°Brix), total sugar (9.20 %), reducing sugar (4.83 %), non-reducing sugar (4.37 %), fruit pH (5.50), whereas minimum stone  weight (0.82 g) and fruit drop (49.38 %) were recorded with application of nano nitrogen @ 2 ml/ litter water + nano phosphorus  @ 2 ml/ litter water spray over the control.
Keywords: Ascorbic acid; Arid climate; Nano nitrogen; Nano Phosphorus; Total sugar